Water Efficiency Using Drip Irrigation Method On Lettuce Plant Growth - Muhammad Fadil; Suwati Suwati; Budy Wiryono; Muliatiningsih Muliatiningsih (Universitas Muhammadiyah Mataram, 2024)
Simple Drip Irrigation is automatic and cheap plant watering. Simple Drip Irrigation is a plant watering technique that uses a water reservoir or water reservoir can be a used bottle that is given a channel to drip the planting media little by little constantly, so that the planting media remains fulfilled its water needs, without becoming muddy and the water supply remains sufficient. This study aims to determine the water efficiency by using drip irrigation method on the growth of lettuce plants. The method used in this research is an experimental method using a Randomised Group Design (RAK) consisting of 3 treatments, namely 3 replications so as to obtain 12 experimental units, first P1 = 300ml water application, second P2 = 200ml water application, and P3 = 100ml water application and analysed using analysis of variance (Anova) at a real level of 5% and if there is a treatment that has a real effect then a test is carried out using the honest real difference test (BNJ) at a real level of 5%. The results of field research conducted by researchers that the provision of drip irrigation has no significant effect on the parameters of plant height, dry trimmed weight, stem diameter, soil texture but significantly different on wet trimmed weight and for the best treatment obtained in the P2 treatment which produces the highest wet trimmed weight of 93 grams.